Regulation of Tumor Immunity by Lysophosphatidic Acid - Lee, Sue Chin; Dacheux, Mélanie A.; Norman, Derek D.; Balázs, Louisa; Torres, Raul M.; Augelli-Szafran, Corinne E.; Tigyi, Gábor J. (Cancers, 2020)
The tumor microenvironment (TME) may be best conceptualized as an ecosystem comprised of cancer cells interacting with a multitude of stromal components such as the extracellular matrix (ECM), blood and lymphatic networks, fibroblasts, adipocytes, and cells of the immune system. At the center of this crosstalk between cancer cells and their TME is the bioactive lipid lysophosphatidic acid (LPA). High levels of LPA and the enzyme generating it, termed autotaxin (ATX), are present in many cancers. It is also well documented that LPA drives tumor progression by promoting angiogenesis, proliferation, survival, invasion and metastasis. One of the hallmarks of cancer is the ability to modulate and escape immune detection and eradication. Despite the profound role of LPA in regulating immune functions and inflammation, its role in the context of tumor immunity has not received much attention until recently where emerging studies highlight that this signaling axis may be a means that cancer cells adopt to evade immune detection and eradication. The present review aims to look at the immunomodulatory actions of LPA in baseline immunity to provide a broad understanding of the subject with a special emphasis on LPA and cancer immunity, highlighting the latest progress in this area of research.